An Analisys Figurative Language in Frozen 2 - Viviana Dhea Indah Vironika; Nur Hidayat; Dyah Nugrahani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study focuses to figurative found in Frozen 2 movie, Descriptive method is used in this research, the data source of this research is the script of the movie Frozen 2. The researcher finds 36 sentences containing figurative language in the movie Frozen 2. All these terms are divided into nine categories, namely simile, metaphor, hyperbole, personification, metonimia, repetition, alliteration, irony, and lithotes. Researchers finds more types of figurative language containing repetition, there are 10 sentences finds in the movie Frozen 2. By reading this research, the researcher hopes that this research can provide readers with a deeper understanding of figurative language analysis. The researcher hopes that this research can provide inspiration for students who want to conduct research in the same field. This research shows readers the types of figurative language found in the movie Frozen 2.